Numerical Solution for Solving Space-Fractional Diffusion Equations using Half-sweep Gauss-seidel Iterative Method - A Sunarto; J Sulaiman; A Saudi (IAES Indonesia Section, 2015)
The main purpose of this paper is to examine theeffectiveness of Half-Sweep Gauss-Seidel (HSGS) method forSpace-Fractional diffusion equations. The Caputo’s derivativeand implicit finite difference scheme will be used to discretizelinear space-fractional equation of the first order to constructsystem linear equation. The basic formulation and application ofthe HSGS iterative method are also presented. Two numericalexamples and comparison with other iterative methods showsthat the present method is effective. Based on computationalnumerical result, the solution obtained by proposed iterativemethod is in excellent agreement, it can be concluded that theproposed iterative method is superior to the Full-Sweep Gauss-Seidel (FSGS) iterative method